The Influence of Online Customer Review and Digital Marketing on Online Purchasing Decision for Beauty Products with Brand Trust as an Intervening Variable: Study of Cirebon Students - Intan Pramita Dewi; Siti Juleha; Mohamad Zaenal Abidin; Yusuf (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to ascertain the influence of digital marketing and online customer reviews on decisions made about purchases made online through brand trust. This study employs a quantitative approach to data analysis, utilizing SmartPLS 3.0 software to support Structural Equation Modeling (SEM) based on Partial Least Square (PLS). By giving out questionnaires to 85 Cirebon students who had made online purchases of cosmetics, primary data was gathered. The study's findings indicate that both digital marketing and online customer reviews have a big impact on brand trust and online customer reviews have an impact on online purchase decisions. Furthermore, it was discovered that brand trust significantly affects judgments made when making purchases online. Additionally, brand trust can act as a mediator between digital marketing and online customer evaluations on judgments made when shopping online. Investigating additional factors that can help achieve this objective is crucial. These variables should be further investigated by future scholars.